(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The biosensor are the analytical instrument that transforms biological reactions into electrical signals. They include tissue-based enzyme-based, DNA biosensors, immune sensors, piezoelectric, thermal, and biosensors. Biosensors may be utilized in a number of agricultural applications, such as assessing toxins in soils and crops, detecting and diagnosing infectious illness in crops and animals, on-line monitoring of key food process parameters, measuring animal reproduction, and screening for veterinary drugs. This article investigates biosensors, their kinds, and their applications. This paper also discusses agriculture and the application of biosensors in agriculture, among other topics. To make cell and tissue-based biosensors, genetically engineered proteins are injected into cells ex vivo or in vivo. They allow the researcher to constantly and noninvasively detect levels of hormones, medicines, or poisons using bio photonics or other physical principles. In this regard, the spectrum may be useful in the field of aging research in the future.